2012
DOI: 10.1139/e11-076
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogic evidences of a mid-Paleozoic tectono-thermal event in the Zonguldak terrane, northwest Turkey: implications for the dynamics of some Gondwana-derived terranes during the closure of the Rheic Ocean

Abstract: The Zonguldak terrane is a Gondwana-derived continental microplate along the Black Sea coast in northwest Anatolia. It includes a Cadomian basement, with oceanic- and island-arc sequences, unconformably overlain by siliciclastic rocks of Ordovician to Middle Silurian age. After a period of deformation and erosion, late Lower Devonian (Emsian) quartzites and shallow-marine limestones unconformably cover Middle Silurian (Wenlock) graptolitic shales. Along several cross sections across the unconformity plane, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…The Early Devonian magmatism, thus, was triggered by accretion of an island arc to the Laurussian margin (Franke, ). Such tectonic settings may explain the differences between Zonguldak and Istanbul (sensustricto) terranes in the Pontides, where the Early Devonian tectonothermal event is recorded by Paleozoic sedimentary rocks of the Zonguldak, but not by the neighboring Istanbul terrane (Bozkaya et al, ).…”
Section: Phases Of Accretion Of Peri‐gondwanan Terranes To Laurussiamentioning
confidence: 99%
“…The Early Devonian magmatism, thus, was triggered by accretion of an island arc to the Laurussian margin (Franke, ). Such tectonic settings may explain the differences between Zonguldak and Istanbul (sensustricto) terranes in the Pontides, where the Early Devonian tectonothermal event is recorded by Paleozoic sedimentary rocks of the Zonguldak, but not by the neighboring Istanbul terrane (Bozkaya et al, ).…”
Section: Phases Of Accretion Of Peri‐gondwanan Terranes To Laurussiamentioning
confidence: 99%
“…However, it may be suggested that these tephra layers were formed in relation with arc-volcanism, generated by the closure of the Variscan Rheic Ocean (Nzegge et al, 2006;Okay et al, 2010;Bozkaya et al, 2012).…”
Section: Regional Geological Settingmentioning
confidence: 99%
“…The formation is overlain by a sequence of more than 500 m thick of alternating limestones and shales (Figures 1c and 2, Madendere and Karadon formations), followed by flood-plain deposits with numerous coal-stems of Westphalian age (Kerey, 1984). Bozkaya et al, 2012). (c) Geological map of the study area and geographic settings of sampling quarries (modified from Akbaş et al, 2002).…”
Section: Regional Geological Settingmentioning
confidence: 99%
“…Ghienne et al 2010 and references therein), fossil data from the Lower and Middle Ordovician rocks are relatively scarce in the Istanbul and Zonguldak terranes of NW Anatolia (e.g. Yanev et al 2006;Bozkaya et al 2012). In the Eastern part of the Zonguldak Terrane, the Safranbolu-Karadere area (Fig.…”
Section: Introductionmentioning
confidence: 99%